2020
DOI: 10.1177/0300060520977416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different interventions for the treatment of postherpetic neuralgia: a Bayesian network meta-analysis

Abstract: Objective We aimed to perform a network meta-analysis that combined both direct and indirect evidence to compare the relative efficacy of interventional therapies to treat patients with postherpetic neuralgia (PHN) and to determine the treatments’ superiority and validity. Method A conventional paired meta-analysis was performed. This was followed by a network meta-analysis using the Bayesian framework. Results Botulinum toxin type A and pulsed radiofrequency (PRF) were the two most effective individual interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…This allows PRF to ease PHN without changing the nerve fiber structure (23,24). In this study, pain was relieved after PRF therapy, which is consistent with the findings of previous studies (10)(11)(12)(13). However, other studies reported that PRF therapy efficacy in treating PHN was not ideal (14,15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This allows PRF to ease PHN without changing the nerve fiber structure (23,24). In this study, pain was relieved after PRF therapy, which is consistent with the findings of previous studies (10)(11)(12)(13). However, other studies reported that PRF therapy efficacy in treating PHN was not ideal (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…However, there are different opinions about the effectiveness of PRF therapy for PHN. Some reports believe that PRF can effectively relieve pain and improve the quality of life of patients with PHN (10)(11)(12)(13). Other reports suggest that PRF is not the ideal therapy for treating neuropathic pain (14) and that PRF does not significantly relieve nerve root pain (15).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical puncture and PRF may cause transient nerve edema and pain aggravation ( 35 ), and PRF treatment has a slower onset ( 2 ). Thus, the combined application of PRF and nerve block in this study will achieve better therapeutic effects ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 90%
“…Regular anti-neuropathic drug administration combined with interventional therapies is widely accepted in ZAP treatment. PRF is easily accepted as an appropriate intervention by both patients and physicians for its proven therapeutic effects, minimal invasiveness, and fewer adverse effects [ 8 ]. Although the mechanisms of PRF remain unclear, various researchers have been working toward revealing the underlying processes.…”
Section: Discussionmentioning
confidence: 99%